La ‘traduction supposée’ ou: de la place des pseudotraductions poétiques en France - Lombez, Christine (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
A pseudo-translation is a fiction, an original text that the author chose to present as a genuine translation for either psychological (e.g. to be acknow-ledged as a writer), ideological (to convey potentially polemic contents with-out being directly involved oneself) or literary reasons (to import new literary patterns supposedly belonging to another tradition). Romantic French poets such as Mérimée, Nodier , Rabbe, and Nerval saw fictitious translations as a way of experimenting with new poetic devices and of freeing themselves from what they regarded as the narrow conventions inherited from French Classicism. My intention in this paper is to contextualize the practice of pseudo-translations in France and in Europe, and to analyze to which extent pseudo-translations of poetical texts contributed to major changes in 19th-century French poetics, be it through the promotion of a new conception of poetry, the introduction of so-called ‘free verse’, or the creation of a new genre: the prose poem.